2015
DOI: 10.1002/pd.4636
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mosaicism for a large segmental duplication of 18q as a secondary finding following non‐invasive prenatal testing and implications for test accuracy

Abstract: Non-invasive prenatal testing (NIPT) for fetal aneuploidies by massively parallel sequencing has transformed the approach to prenatal care. The presence of circulating fetal cell-free DNA (cfDNA) in maternal plasma, which is derived primarily from the placenta, is the basis of this test.1 Studies comparing NIPT to serum or combined screening have shown that NIPT outperforms these screening options in trisomy detection and has significantly lower false positive rates. 2-4 Biological causes of false positive NIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…For the 42 discordant cases with normal fetal karyotypes and no reported maternal disease, the NIPT result might reflect CPM, residual cfDNA from an unrecognized vanished twin, or a maternal copy number variant . Grati et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the 42 discordant cases with normal fetal karyotypes and no reported maternal disease, the NIPT result might reflect CPM, residual cfDNA from an unrecognized vanished twin, or a maternal copy number variant . Grati et al .…”
Section: Discussionmentioning
confidence: 99%
“…For the 42 discordant cases with normal fetal karyotypes and no reported maternal disease, the NIPT result might reflect CPM, 19 residual cfDNA from an unrecognized vanished twin, 20 or a maternal copy number variant. 21,22 Grati et al determined the potential contribution of CPM to the NIPT false-positive rate, demonstrating that chromosomes 13 and X were more likely to be associated with CPM than chromosomes 18 and 21. 23 There was one suspected case of CPM in our dataset, a partially concordant case that had postnatal placental analysis.…”
Section: Discussionmentioning
confidence: 99%
“…35 More recently, it has become appreciated that both small maternal duplications (CNVs) and larger mosaic maternal duplications can cause false-positive cfDNA results for autosomal aneuploidy. 44,46,47 Other maternal conditions, such as a prior solid organ transplant from a male donor, 48 have been shown to be the etiology for discordant sex chromosome cfDNA results. Subclinical organ rejection results in the release of cfDNA into the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Follow‐up case studies of false‐positive NIPT results has identified a variety of potential causes including a vanishing twin, unidentified maternal tumors, maternal mosaicism, and confined placental mosaicism . More recently, several groups using different NIPT methodologies have reported maternal copy number variations (CNVs) as an additional cause of false‐positive NIPT results . In order to further investigate the potential contribution of maternal CNVs to false‐positive NIPT results, we performed NIPT on a large cohort of 112 021 pregnant women using low coverage massively parallel sequencing and analyzed the 74 false‐positive trisomy samples for the presence of maternal CNVs.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] More recently, several groups using different NIPT methodologies have reported maternal copy number variations (CNVs) as an additional cause of false-positive NIPT results. 6,[21][22][23][24][25][26] In order to further investigate the potential contribution of maternal CNVs to false-positive NIPT results, we performed NIPT on a large cohort of 112 021 pregnant women using low coverage massively parallel sequencing and analyzed the 74 falsepositive trisomy samples for the presence of maternal CNVs.…”
Section: Introductionmentioning
confidence: 99%